2017
DOI: 10.1136/sextrans-2016-052988
|View full text |Cite
|
Sign up to set email alerts
|

Impact of deploying multiple point-of-care tests with a ‘sample first’ approach on a sexual health clinical care pathway. A service evaluation

Abstract: ObjectivesTo assess clinical service value of STI point-of-care test (POCT) use in a ‘sample first’ clinical pathway (patients providing samples on arrival at clinic, before clinician consultation). Specific outcomes were: patient acceptability; whether a rapid nucleic acid amplification test (NAAT) for Chlamydia trachomatis/Neisseria gonorrhoeae (CT/NG) could be used as a POCT in practice; feasibility of non-NAAT POCT implementation for Trichomonas vaginalis (TV) and bacterial vaginosis (BV); impact on patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 24 publications
0
45
0
Order By: Relevance
“…One study that evaluated the use of point-of-care NAAT testing with a 90-min TAT for gonorrhea and chlamydia in an STI clinic in England found that results were available for only 21.4% of patients while they were in the clinic (45). Patient treatment was modified in 3 of 15 patients with available results, and the patients reported high satisfaction (>90%) with the test-and-treat strategy.…”
Section: Stismentioning
confidence: 99%
“…One study that evaluated the use of point-of-care NAAT testing with a 90-min TAT for gonorrhea and chlamydia in an STI clinic in England found that results were available for only 21.4% of patients while they were in the clinic (45). Patient treatment was modified in 3 of 15 patients with available results, and the patients reported high satisfaction (>90%) with the test-and-treat strategy.…”
Section: Stismentioning
confidence: 99%
“…Another study looked at the impact of the 90-minute Xpert CT/NG test when sample collection was performed on arrival of the patient, with the intention being that the patients receive their results and treatment as needed during the appointment [8]. Actual wait times were evaluated.…”
Section: Turnaround Time and Patient Impactmentioning
confidence: 99%
“…The development of point-of-care tests (POCTs) for an STI such as gonorrhea is recognized as a vital approach to improve timely diagnosis [ 13 , 14 , 20 , 21 , 22 ]. Although POCTs are commercially available for the diagnosis of N. gonorrhoeae , many of these tests do not fit the ASSURED criteria important for STI diagnosis tests, such as affordability, sensitivity, specificity, user friendliness, robustness, and rapidness [ 13 , 21 ].…”
Section: Introductionmentioning
confidence: 99%